Random House Webster's college dictionary. (Random House, 1999)
Extensive dictionary features and content in one user-friendly program. Over 87,000 entry words; more than 207,000 definitions . 4 powerful search options; crossword help; Spellcheck Plus. Drag-and-drop words for instant definitions; easy to use. Instant Windows interface; help page for phonetic symbols